Studying WeChat Official Accounts with novel 'backend-in' and 'traceback' methods: Walking through platforms back-to-front and past-to-present. (August 2022) - Yang, Fan; Heemsbergen, Luke; Marshall, P. David
The paper presents a methodology to understand WeChat Official Accounts (WOAs) from their backend to their frontend, and from tracing the platform's history to its present. Our 'Backend-in method' proposes to study platform governance in the meso – between macro political economic concerns and the micro (and usually mobile) user-interface mediation. It shows how including backend platform media practices deepen ethnographic understandings of platform use. The 'Traceback method' uses researcher-informant collaboration to document and reflect on the shifts of platform affordances that have reconfigured media practices, organisational structures, and economic incentives over time. We show how these methods proved useful in mapping Chinese-Australian media organisations' deployment of WOAs for news production. Together these methods contribute ways to understand previously hidden aspects of media practice and platform governance in a novel methodological design, which may have wider application for future research.